Cyclic gb(B-Glucans from Microorganismss Production, Properties and Applications - Venkatachalam, Geetha; Gummadi, Sathyanarayana; Doble, Mukesh; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
to Cyclic glucans are polysaccharides that are predominantly produced by Agrobacterium, Bradyrhizobium and Rhizobium sp. and widely used in the pharmaceutical and food industries. In this book, the applications, properties, analytical tools, production and genes of four main cyclic gb(B-glucans from microorganisms are highlighted and critically evaluated. As biocompatible and biodegradable renewable resources, they have an immense potential for future applications, which has not yet been fully exploited. This concise review will help to bridge this gap.s
Keywords: Life sciences; Pharmaceutical technology; Microbiology; Food science; Life Sciences; Microbiology; Applied Microbiology; Food Science; Pharmaceutical Sciences/Technology.